Preservação de plasma rico em plaquetas de coelhos em nitrogênio líquido e freezer - Vieira, Raissa Brauner Kamla (2017)
Platelet rich plasma (PRP) is a blood by-product obtained from centrifugations and subsequent separation of blood elements. Platelets are responsible for the production and release of factors that favor the repair of different tissues. This study aimed to compare and evaluate the viability of PRP after freezing and cryopreservation. Twelve healthy adult New Zealand rabbits were used to collect 12 mL of blood from each animal through cardiac puncture. Centribio centrifuge with 14 cm in diameter was used for the freezing protocol, and Centurion Scientific K3 Series cold centrifuge at 4 ° C 18 cm in diameter was used for the nitrogen preservation protocol. For both protocols, two centrifugations were done at 2000 rpm for 20 minutes each. The obtained PRP was submitted to two preservation protocols, one being the freezing at -20 ° C (protocol F) and the other the gradual reduction of temperature to cryopreservation at -196 ° C (protocol N). In both protocols were used 6% DMSO as cryoprotectant and analysis made at zero (0) times and after 15, 30, 45 and 60 days after preserved. Neubauer chamber counts were performed, tests of 3- (4,5-dimethylthiazol-2yl)-2,5-diphenyl tetrazoline bromide (MTT) for cell viability, SDS-PAGE electrophoresis for protein identification and culture for fungi and mesophiles. It was verified that PRP preserved under N protocol had a higher number of platelets preserved when compared to protocol F (p <0.05). In the MTT test, the N protocol showed greater metabolic variation, but a higher platelet viability, confirmed by electrophoresis, where protein prevalence was observed in the cryopreserved samples. At the microbiological test, all the samples were free of contaminants of bacterial and fungal origin. The preservation method in liquid nitrogen was more effective than in freezer, keeping platelets more active metabolically, tissues repairing proteins presents and sterility.